Copper and cobalt recovery from pyrite ashes of a sulphuric acid plant. Issue 6 (June 2016) - Erust, Ceren; Akcil, Ata
The pyrite ashes formed as waste material during the calcination of concentrated pyrite ore used for producing sulphuric acid not only has a high iron content but also contains economically valuable metals. These wastes, which are currently landfilled or dumped into the sea, cause serious land and environmental pollution problems owing to the release of acids and toxic substances. In this study, physical (sulphation roasting) and hydrometallurgical methods were evaluated for their efficacy to recover non-iron metals with a high content in the pyrite ashes and to prevent pollution thereby. The preliminary enrichment tests performed via sulphation roasting were conducted at different roasting temperatures and with different acid amounts. The leaching tests investigated the impact of the variables, including different solvents, acid concentrations and leach temperatures on the copper and cobalt leaching efficiency. The experimental studies indicated that the pre-enrichment via sulphation roasting method has an effect on the leaching efficiencies of copper and cobalt, and that approximate recoveries of 80% copper and 70% cobalt were achieved in the H2 O2 -added H2 SO4 leaching tests.